Decomposition of native cyclodextrins and cyclodextrin derivatives by various Trichoderma species - Gyula Oros (ՀՀ ԳԱԱ հրատ.)
The growth and the development of thallus of 14 Trichoderma species have been determined by using native a-,β- and γ-cyclodextrins(CDs)and 8 different CD derivatives as a unique carbon source.
Keywords: Biology; Biochemistry